Modification of Proteins by Norepinephrine is Important for Vascular Contraction - Johnson, Kyle B.; Thompson, Janice M.; Watts, Stephanie W. (Frontiers in Physiology, 2010)
Norepinephrine (NE) is thought to mediate its effects through G-protein coupled receptors. However, previous studies have shown that norepinephrine and another primary amine, serotonin, also have the ability to exert effects in a receptor-independent manner. We hypothesized that the enzyme transglutaminase II (TG II) has the ability modify proteins with NE and that this modification is physiologically relevant. As our model we used rat aortic and vena cava tissues, two tissues that depend on NE to modulate vascular tone. Immunohistochemical and immunocytochemical staining showed that NE and TG II are present in smooth muscle cells of these tissues. Western analysis shows aorta and vena cava homogenate proteins are recognized by an anti-NE antibody. NE and α-actin colocalize in cultured aorta and vena cava smooth muscle cells. Freshly dissociated smooth muscle cells from these vessels were able to take up NE-biotin. In isolated tissue baths, inhibition of TG II with cystamine (0.5 mM) completely abolished NE-induced contraction in the aorta but only attenuated the receptor-independent contractant KCl (max contraction to 100 mM KCl in cystamine treated = 88.8 ± 7.5% of vehicle treated, p<0.05). In the vena cava, contraction to NE was abolished with 0.1 mM cystamine and KCl contraction was attenuated (max contraction to 100 mM KCl in cystamine treated = 54.8 ± 21.2% of vehicle treated, p<0.05). Taken together, these results show that vascular smooth muscle cells take up and utilize NE for the modification of proteins, and that this modification may play an important role in vascular contraction.